2011
DOI: 10.1093/cercor/bhr022
|View full text |Cite
|
Sign up to set email alerts
|

Musical Expertise Boosts Implicit Learning of Both Musical and Linguistic Structures

Abstract: Musical training is known to modify auditory perception and related cortical organization. Here, we show that these modifications may extend to higher cognitive functions and generalize to processing of speech. Previous studies have shown that adults and newborns can segment a continuous stream of linguistic and nonlinguistic stimuli based only on probabilities of occurrence between adjacent syllables or tones. In the present experiment, we used an artificial (sung) language learning design coupled with an ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
104
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 60 publications
8
104
2
Order By: Relevance
“…This process is not complete until young adulthood, by which time N1 has become the largest component in the cortical response to sound (17,18,(21)(22)(23). In adults, music training amplifies the N1 response (53)(54)(55)(56). Here, we find an increase in N1 amplitude relative to P1 amplitude only in the music group.…”
Section: Discussionmentioning
confidence: 52%
“…This process is not complete until young adulthood, by which time N1 has become the largest component in the cortical response to sound (17,18,(21)(22)(23). In adults, music training amplifies the N1 response (53)(54)(55)(56). Here, we find an increase in N1 amplitude relative to P1 amplitude only in the music group.…”
Section: Discussionmentioning
confidence: 52%
“…Implicit learning plays an important role in the acquisition of complex structural knowledge, both in language (e.g., Saffran, Aslin, & Newport, 1996;see Kuhl, 2004, for a review) and in music (e.g., Ettlinger, Margulis, & Wong, 2011;Loui, Wu, Wessel, & Knight, 2009;Loui, Wessel, & Husdon Kam, 2010;Loui, 2012;Rohrmeier & Rebuschat, 2012). Support for shared reliance on implicit learning mechanisms comes from the finding that musical training (which presumably places additional demands on implicit learning mechanisms) leads to better implicit learning of both musical and linguistic structure (Francois & Schön, 2011). Working memory has also been linked to processing of syntax in language (e.g., Just & Carpenter, 1992;Lewis et al, 2006) and in music (Koelsch et al, 2009;Schulze et al, 2011;Williamson et al, 2010), and is associated with the inferior frontal regions that are implicated in both domains (Koelsch et al, 2009;Schulze, Zysset, Mueller, Friederici, & Koelsch, 2011; but see Fedorenko et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While most studies suggested that explicit learning is more effective than implicit learning, these studies measured the learning effects using behavioral tests that may favor explicit learning such as short-term learning. Other studies suggested that the learning effects depend on the learner's prior knowledge (Francois & Schön, 2011;Gass, Svetics, & Lemelin, 2003). Thus, we cannot precisely determine which learning process is more effective (DeKeyser, 2003;Ellis, 2009).…”
Section: Implicit and Explicit Knowledgementioning
confidence: 90%
“…Thus, we cannot precisely determine which learning process is more effective (DeKeyser, 2003;Ellis, 2009). Interestingly, some earlier studies claimed that knowledge of music and language is acquired largely by implicit learning (Ettlinger, Margulis, & Wong, 2011;Francois & Schön, 2011;Krashen, 1982). Reber (1989) argued that implicit learning is the fundamental process that lies at the heart of the adaptive behavioral repertoire of every complex organism, while Dekeyser claimed that implicit learning is essential for adaptation to the environment (Reber, 1993).…”
Section: Implicit and Explicit Knowledgementioning
confidence: 99%